Gain enhancement and sidelobe level reduction of rectangular microstrip patch antenna under operation of high-order modes - Bernardo, Helton Silva [UNESP] (2024)
Emerging technologies are revolutionizing the market with advanced devices and increased data transmission power, thereby enhancing wireless connectivity performance. Furthermore, microstrip patch antennas (MPAs) are lightweight, compact, and can be easily integrated into flat surfaces, making them ideal for mobile devices and embedded communication systems, providing higher gain and directivities on higher-order modes. But, this operation involving higher sidelobe levels that it is problematic issue. In order to mitigate these problem, we propose two easy and simplest techniques: using slots and stubs method and permittivity analysis. Moreover, our study proposes an MPA operating in the TM50-like mode to achieve higher gain and lower sidelobe levels. Our methodology involves altering the surface current distribution of the resonator by introducing three sets of transverse slots at points of null electric field. We fabricated and characterized an antenna prototype resonating at 7.6 GHz in the C-band. The results demonstrate an increased realized gain of 15.0 dBi and reduced sidelobe levels to approximately 15 dB. Additionally, we present another technique focusing on permittivity analysis aimed at reducing sidelobe levels by adjusting the permittivity for a microstrip patch antenna operating in the TM30-mode. The findings reveal a significant reduction in sidelobe levels to -33 dB, while maintaining a constant directivity of 10 dBi—a standard value. Minor decreases were noted in both the effective area and aperture efficiency. Furthermore, we reduce the physical and effective size of the antenna in a conventional MPA project operating at 7.3 GHz. This is done to compare the performance of two evaluation methods: slots and stubs versus permittivity analysis. The gain-over-area metrics have demonstrated that the permittivity analysis yields significantly better results, showing a difference of 7 units (inverse wavelength in free-space squared) compared to the slots and stubs method (reduced SLL ~ 13.3 dB) method and permittivity analysis (reduced SLL ~ 12.7dB) both equivalently efficient.